Does an Undergraduate Aging and the Aged Course Have an Impact On Students' Attitudes Towards Working With Older Adults? - Gibson, Patricia A. (My University, 2015)
The purpose of this study was to better understand undergraduate students' attitudes toward older adults, as well as to find out whether taking a course on aging impacts students' attitudes towards older adults.
Color poster with text and photographs.
Keywords: Aging population (U.S.); Social work; College students; Elderly people; Older adults; Posters